Reconciliation Between Executive and Legislative Powers in a Presidential System of Government: A Case Study in Indonesia - Isnaeni, Belly; Sofwan, Edi (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This research aims to analyze the reconciliation between executive and legislative powers within Indonesia's presidential system. By examining the dynamic relationship between these two branches of power, the study focuses on the challenges and solutions for creating effective synergy. A qualitative research method was employed, utilizing document analysis and interviews with experts. The findings highlight the critical importance of dialogue and collaboration in strengthening political stability and national development. This study concludes that constructive dialogue and collaborative policies are essential to overcome existing challenges and foster a more stable and effective governance in Indonesia.